Здобутки та нові виклики у діяльності системно важливих банків в Україні - Владика, Юлія Павлівна; Vladyka, Julia; Безугла, Людмила Сергіївна; Bezuhla, Liudmila; Турова, Лариса; Turova, Larisa (Причорноморський науково-дослідний інститут економіки та інновацій, 2020)
У статті розкрито питання функціонування системно важливих банків та їх значення для забезпечення стабільності національних банківських систем та глобальної фінансової системи з метою підтримання економіки в умовах фінансово-економічної кризи та забезпечення економічного й соціального розвитку. Результати дослідження доводять, що системно важливі банки істотно впливають на стабільність банківського та фінансового секторів, а тому центральні банки щороку визначають перелік системно важливих банків та здійснюють нагляд за їхньою діяльністю. Проаналізовано фінансові показники системно важливих банків і виявлено, що банки суттєво відрізняються за розмірами активів, обсягами чистого прибутку. Висвітлено особливості державного регулювання системно важливих банків в Україні. Окрему увагу приділено використанню маркетингових інструментів у забезпеченні конкурентоспроможності банків на ринку фінансових послуг у період настання нової фінансової кризи. A reliable banking system is an important condition for ensuring the country’s financial stability, sustainable economic development and welfare as it provides the flow of financial resources, promotes entrepreneurship and technological advances, improves the quality of people’s lives and leads to economic benefits to individuals and society. But, banking activity has been suffering from threats. No country can achieve sustainable economic development without systemically important banks. The purpose of the article is to study the trends of banking activities of systemically important banks in Ukraine, as well as to identify achievements and new challenges in the activities of systemically important banks in Ukraine. The methods of structural and logical analysis were used to implement theoretical generalizations and formulation of trends of banking activities of systemically important banks in Ukraine. The methods of detailing and synthesis were used to study financial performance of systemically important banks in Ukraine. The method of theoretical generalization was used in the formulation of proposals and conclusions. A systemically important bank is a bank, whose failure might trigger a financial crisis and lose a large part of value. The article researches introduction and application of main criteria of definition of systemically important banks in the EU and world such as size, cross-jurisdiction activity, complexity, and substitutability. It is concluded that banking activity of systemically important banks are aimed at coordinating the financial policies of countries in order to ensuring a financial stability and supporting sustainable economic and social development. Particular importance is attached to monitoring of financial performance of systemically important banks in Ukraine. Considerable attention is paid to achievements and new challenges in the activities of systemically important banks in Ukraine. It is noted that an integral part of banking activity of systemically important banks during the new financial crisis of 2020 are promotion of non-cash payments, development and implementation of new products for individual groups of customers, development and implementation of central bank strategies and others.
Achievements and new challenges in the activities of systemically important banks in Ukraine
Keywords: банківська система; banking system; системно важливі банки; systemically important banks; фінансова стабільність; financial stability; фінансово-економічна криза; financial and economic crisis; здобутки банків; achievements of banks; регулювання банківської діяльності; regulation of banking activity; маркетингова політика банків; marketing policy of banks